A case of gastrointestinal stromal tumor presenting with small bowel perforation and internal hernia - Volkan ÖZBEN; Sinan Çarkman; Deniz ATASOY; Gülen DOĞUSOY; Erhun EYÜBOĞLU (Turkish Journal of Gastroenterology, 2019)
-